Revolutionizing Tuberculosis Treatment Adherence through a Web-Based Reminder System: Revolusi Kepatuhan Pengobatan Tuberkulosis melalui Sistem Pengingat Berbasis Web - Nadia Falakhis Salsabilah; Irwan Alnarus Kautsar (Academia Open, 2024)
This research develops a website-based reminder system using the Waterfall Method and WhatsApp for message notifications, aiming to improve patient adherence to treatment plans, particularly for conditions like Tuberculosis (TB) that require strict medication schedules. The study evaluates the system's functionality and user satisfaction, with positive feedback indicating strong agreement (56.5%) and agreement (39.1%) among respondents regarding the system's effectiveness. Key advantages include 24/7 active server support, technical assistance via instant messaging, flexible usage, and fast delivery of notifications, showcasing its potential in enhancing healthcare communication and treatment compliance. Highlight: Website reminder system for treatment adherence with Waterfall Method. Patient satisfaction and communication improvement through WhatsApp integration. 24/7 server support, fast notifications, and enhanced patient engagement. Keyword: Reminder system, Waterfall Method, Patient adherence, Healthcare communication, Treatment compliance